Cloud ERP: An Overview - Rakshit, D; Chatterjee, P (International Journal of Computer Sciences and Engineering, 2025)
In the current market practice, cloud ERP application has gained momentum with the changing market scenario. Companies are evolving with cloud platform with low initial investment. This study aims to depict the current scenario of the cloud ERP market and their offerings and further implementing issues with a greater focus on strategic business process